2018
DOI: 10.1101/255265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A saturation mutagenesis approach to understanding PTEN lipid phosphatase activity and genotype-phenotypes relationships

Abstract: Phosphatase and tensin homolog (PTEN) is a tumor suppressor frequently mutated in diverse cancers. Germline PTEN mutations are also associated with a range of clinical outcomes, including PTEN hamartoma tumor syndrome (PHTS) and autism spectrum disorder (ASD). To empower new insights into PTEN function and clinically relevant genotype-phenotype relationships, we systematically evaluated the effect of PTEN mutations on lipid phosphatase activity in vivo. Using a massively parallel approach that leverages an art… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
(102 reference statements)
1
14
0
Order By: Relevance
“…Finally, because it is technically challenging to functionally interrogate all germline and somatic PTEN mutations, research efforts have focused on devising high-throughput methods to evaluate pathogenicity. Surprisingly, several residues within the catalytic pocket are shown to be tolerant to mutations, with solvent exposure playing a critical role in dictating tolerance (80). Moreover, several uncharacterized PTEN variants result in decreased PTEN thermodynamic stability and abundance, thus expanding the list of potentially functional variants (81).…”
Section: Pten Dysfunction and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, because it is technically challenging to functionally interrogate all germline and somatic PTEN mutations, research efforts have focused on devising high-throughput methods to evaluate pathogenicity. Surprisingly, several residues within the catalytic pocket are shown to be tolerant to mutations, with solvent exposure playing a critical role in dictating tolerance (80). Moreover, several uncharacterized PTEN variants result in decreased PTEN thermodynamic stability and abundance, thus expanding the list of potentially functional variants (81).…”
Section: Pten Dysfunction and Cancermentioning
confidence: 99%
“…Such effects cannot be extrapolated from PTEN's secondary structure alone and indeed provide an important dimension to consider for assessing PTEN genotype-PHTS phenotype associations. Additionally, studies have shown that ASD-associated mutations tend to retain higher PTEN activity relative to non-ASD-associated mutations (80,89,90). Whether assayed in vivo in yeast or in vitro in mammalian stable or primary cell lines, partial hypomorphic PTEN lipid phosphatase activity is retained in individuals with ASD, versus total loss of PTEN lipid phosphatase activity in individuals with more severe PHTS-related phenotypes (80,(89)(90)(91).…”
Section: Genotype-phenotype Correlations and Modifiers Of Cancer Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Several such exhaustive sequence-function maps have been recently been generated in 448 yeast and human cell culture systems (Findlay et al, 2018(Findlay et al, , 2014Majithia et al, 2016;449 Matreyek et al, 2018;Mighell et al, 2018;Weile et al, 2017). These tools offer amazing 450 resources that serve as 'lookup tables' of functional missense variation in human genes, to 451 enable experimentally confirmed variant interpretation immediately upon first clinical 452 presentation (Starita et al, 2017;Weile et al, 2017).…”
Section: Further Applications Of Targeted Human Gene Replacement 409mentioning
confidence: 99%
“…130 phenotypes (collectively called PTEN harmatoma tumor syndrome), intellectual 139 disability, and Autism Spectrum Disorders (Hobert et al, 2014;Li et al, 1997;Danny 140 Liaw et al, 1997;McBride et al, 2010;O'Roak et al, 2012;Orrico et al, 2009;Sanders 141 et al, 2015;Varga et al, 2009). Despite extensive study, it is currently impossible to 142 predict the clinical outcome of a PTEN mutation carrier using sequence data alone 143 (Matreyek et al, 2018;Mighell et al, 2018). PTEN also has several technical advantages 144 that make it an ideal test case: 1) PTEN functions in the highly conserved insulin 145 signaling pathway that is well characterized in C. elegans (Ozes et al 2001;Ogg & 146 Ruvkun 1998;Mihaylova et al 1999, and Fig.…”
Section: Introductionmentioning
confidence: 99%